Bledius Leach from southern Brazil (Coleoptera, Staphylinidae, Oxytelinae) - Caron,Edilson (2007)
Three species of Bledius Leach, 1819 are recognized from southern Brazil. A new species is described, B. hermani n. sp., from Paraná and Rio Grande do Sul States and B. fernandezi Bernhauer, 1939 is redescribed. The geographical distribution of B. bonariensis Bernhauer, 1912 and B. fernandezi are extended. A key to identification of Bledius from southern Brazil is also provided.